Blind ambition how to envision your limitless potential and achieve the success you want - Walsh, Patricia 1981- (McGraw-Hill Education, 2015)
Diagnosed with a pediatric brain tumor, Patricia Walsh became partially blind at the age of five. As a teenager, she lost what little vision remained due to surgical complications, and the straight-A student began a downward spiral into depression and hopelessness. She eventually had an epiphany: if she didn't do something, she would doom herself to a life devoid of meaning. Today, Walsh is an award-winning computer engineer and champion paratriathlete. In 2011, she set the world record for blind triathletes, shattering both male and female records by over 50 minutes. Walsh inspires and educates by relating her unforgettable personal story while detailing her proven Fuel/Fire/ Blaze approach to achieving any goal in her book. She shows how to set realistic milestones and describes a simple and effective process for mapping these milestones to daily tasks that will help you achieve what you previously thought unachievable. --
Includes bibliographical references and index. - Print version record
Keywords: Success; Motivation (Psychology); Goal (Psychology); Achievement; Motivation; Succès; Motivation (Psychologie); BUSINESS & ECONOMICS; Motivational